FİNANCİAL PERFORMANCE OF THE BANKİNG SECTOR: A COMPARATİVE STUDY BETWEEN IRAQİ AND TURKİSH COMMERCİAL BANKS (Third Sector Social Economic Review, 2024)
Banks ensure the transfer of capital accumulation within the financial system to the real sector for the development of country economies. This study aimed to evaluate the financial performance of Iraqi and Turkish banks. A total of 16 banks were included in the study between the years 2011-2021 included in the financial reports of the examined banks were analyzed. Panel Data analysis was performed to measure the relationship between two dependent variables (ROA and ROE) and seven independent variables (Total deposits/Total assets (B1), Liquid Assets/Current Liabilities (L1), Loans received/ Total Assets (B2), Liquid Assets (L2), Total loans/ Total assets (A1), Operating Leverage (OL), GDP). For the Turkish banks a positive relationship was found among the ROA and B2, L2, FK. In addition, a negative relationship was found between GDP, A1 and ROA. And also a positive relationship was found among L2, B2, OL and ROE of Turkish Banks. For the Iraqi banks a positive relationship was found among the L2, GDP and ROA; also there is a negative relationship among the A1 and ROA;and there is a positive relationship was found among the OL, GDP and ROE; and there is a negative relationship among the B1, A1 and ROE.
Keywords: Bank Performance; Banking Sector; Financial Statements; Iraqi; Turkey